Price Fluctuations of the Indonesian Sharia Stock Index (ISSI) Influenced by Inflation, FED Rate and BI Rate - Rahma Sofia Nida; Amalina Ghassani; Siti Amaroh; Guijiao Zou (Yayasan Adra Karima Hubbi, 2023)
This research was conducted from the background of fluctuating movements in ISSI prices due to macroeconomic influences, namely inflation and interest rates. Against this background, the purpose of the study is to examine the Indonesian Sharia Stock Index (ISSI) Price for 2018 – 2022 in terms of Inflation, The Fed Rate, and BI Rate. The research method used quantitative with secondary data. Data on Inflation, FED Rate, BI Rate and ISSI Share Price from 2018-2022 are obtained from the official website of related variables. Data is processed with the help of IBM SPSS 26 use multiple linear regression analysis methods. The results of data analysis prove that simultaneously variables of Inflation, FED Rate, and BI Rate significantly affect ISSI Price. The results of the t partially test, give the result that Inflation doesn't significantly affect the ISSI Price. Different results on variable interest rates, significant positive FED Rate and significant negative BI Rate affect the ISSI Price. This can be interpreted that interest rates are still an important reference used by investors for make their decision. The results of this research in the future will hopefully be useful for investors as an additional consideration in deciding to invest in Islamic stocks incorporated in the Indonesian Sharia Stock Index (ISSI).